Association study between C10orf90 gene polymorphisms and colorectal cancer - Song, Jian; Wang, Kaixuan; Chen, Zhaowei; Zhong, Dunjing; Li, Li; Guo, Liangliang; Yu, Shuyong (Frontiers in Oncology, 2023)
Background: Colorectal cancer (CRC) is the third most common malignant tumor in the world. The morbidity and mortality rates in western countries have decreased, but they are still on the rise in China. C10orf90 is associated with a variety of cancers, but the correlation between C10orf90 and CRC is not yet known. Methods: A total of 1339 subjects were randomly enrolled in our study. After extracting their DNA, three SNPs of C10orf90 were genotyped to analyze the potential relationship between these variants and CRC risk. PLINK software packages (version 1.07) were used to evaluate multiple genetic models by calculating odds ratio (OR) and 95% confidence interval (95% CI). The best SNP-SNP interaction model was defined by the multifactor dimensionality reduction (MDR) analysis. Results: C10orf90 rs12412320 was significantly associated with CRC risk (p = 0.006), and might be associated with the lower CRC risk (OR: 0.78; 95% CI: 0.65-0.93). The relationship to the lower CRC risk was found about rs12412320 in people aged >60 years and  60 years, females, non-smokers or non-drinkers. Rs11245008 in people aged  60 years and rs11245007 among males had the higher CRC susceptibility. Rs12412320 was related to the lower risk of advanced stages (III/IV stage), while rs11245007 might be associated with the higher risk of advanced stages (III/IV stage). Moreover, rs12412320 had the most significant relationship with the susceptibility of rectal cancer. Conclusion: This study firstly reported the relationship between C10orf90 gene polymorphisms and CRC risk in Chinese people, which suggest that C10orf90 rs12412320 might be a protective role for CRC occurrence.